1993
DOI: 10.1177/107110079301400807
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Diagnosis of Plantar Fasciitis

Abstract: There is currently no objective reliable diagnostic test for plantar fasciitis inasmuch as diagnosis cannot be made on the basis of finding a heel spur on radiography (x-ray). In this single-blind observational study, ultrasonography was used to measure plantar fascia thickness in subjects with clinically suspected plantar fasciitis and in control subjects. It was concluded that the population mean plantar fascia thickness is greater for people with plantar fasciitis than for people without heel pain (P < .000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
2
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 9 publications
3
67
2
2
Order By: Relevance
“…Although level of physical activity was not measured, it is unlikely that plantar fasciitis, a common condition among athletes, is the cause of fascia thickness. Fasciitis is associated with heel pain, and its ultrasonographic changes are limited to the proximal insertion of the aponeurosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although level of physical activity was not measured, it is unlikely that plantar fasciitis, a common condition among athletes, is the cause of fascia thickness. Fasciitis is associated with heel pain, and its ultrasonographic changes are limited to the proximal insertion of the aponeurosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…1,16,31 The average thickness of the plantar fascia in healthy individuals is between 2.2 and 3.6 mm. 13,30 In patients with plantar fasciitis, it ranges from 4.6 to 6.1 mm. 1,15,16,19 In general, individuals with a plantar fascia thicker than 4 mm are considered to have plantar fasciitis.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] The plantar aponeurosis, similar to tendons elsewhere, is shown sonographically as a homogeneous echogenic band with internal linear interfaces on longitudinal sections. 16 Sonography has also the advantages of being noninvasive, well tolerated by patients, and inexpensive, and it provides excellent spatial resolution for superficial structures. Previous studies reported that mechanical stress and inflammation result in tendon thickening, with hypoechoic areas within the plantar fascia 17 and, occasionally, peritendon fluid collection, 18 but these studies were done in a limited number of patients.…”
mentioning
confidence: 99%